Leadership in Education: Strengthening Human Resources and Learning Outcomes Following the ‘Program Sekolah Penggerak’ Intervention - Sintya, Tira Fitria Astrid Dhica; Awaludin, Dandy Prasetyo; Wibowo, Udik Budi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
“Program Sekolah Penggerak” is a strategic initiative and a challenge for principals in implementing the program, including limited human resources, demands for improving the quality of learning, and adaptation to educational transformation policies. This study aims to analyze principals' strategies after participating in the School Mover program, focusing on improving human resource performance and school learning quality. This study uses a qualitative case study approach. The research informants were three principals participating in the “Program Sekolah Penggerak”. Data analysis was done by summarizing transcripts, presenting information, drawing conclusions and verifying. The results of the study indicate that in improving human resource performance, principals involve teachers and staff in formulating schools (vision, mission, goals), implementing a participatory leadership approach, routinely identifying human resource development needs, building a collaborative culture, and giving awards for the achievements and contributions of teachers and staff. Improving the quality of learning is done by increasing academic standards, improving monitoring and evaluation activities, and optimizing differentiated learning. The leadership model of the principal after the School Mover program facilitation, which was originally instructional, tends towards a transformational leadership model.